MODIFIKASI AMILUM GANYONG (CANNA DISCOLOR LINDL) SECARA ENZIMATIS DENGAN BAKTERI LACTOBACILUS ACIDOPHILUS SEBAGAI EKSIPIEN TABLET - Azhary, Deny Puriyani (Journal of Pharmacopolium, 2018)
Canna starch is one type of starch that has potentially to be used as tablet excipient. Natural canna starch has poor flow properties and compressibility. Therefore, canna starch is modified by enzymatically with Lactobacillus acidophilus (lactic acid bacteria) that can produce α-amylase enzyme. The α-amylase enzyme capable of decomposing and altering microscopic structure of starch then can improve the flow properties and starch compressibility. The aim of this research to know the influence of enzymatically modified with Lactobacillus acidophilus bacteria on physical properties of canna starch. Enzymatically modified was conducted by using Lactobacillus acidophilus 3% (b/v) for 72 hours. The results showed that enzymatically modified using Lactobacillus acidophilus bacteria significantly influence the physical properties of canna  starch, change the particle size of starch, improve the flow properties and compressibility  and can be used as tablet excipient